Corporate Social Responsibility and Firm Value: The Moderating Role of Profitability in Indonesian Consumer Non-Cyclicals - Mutiara Thevany Fayazza; Acep Komara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) on firm value and to examine the role of profitability as a moderating variable in consumer non-cyclicals firms listed on the Indonesian Stock Exchange (IDX) during the period 2022-2024. This study uses a quantitavive approach with an associative research design. The research population includes all consumer non-cyclicals sector companies listed on the IDX. The sample was selected using purposive sampling based on specific criteria, resulting in 14 companies with a total of 42 observations. The data were analyzed using MRA panel data regression with an interaction model to test the moderating role of profitability, proxied by Return On Assets (ROA). Firm value was measured using Tobin’s Q, while CSR disclosure was measured based on the Global Reporting Initiative (GRI) 2021 standards. Empirical testing shows that CSR has a negative and significant effect on firm value. Profitability does not show a direct effect on firm value. However, the CSR×ROA interaction variable has a positive and significant effect, indicating that profitability strengthens the relationship between CSR and firm value. Companies with credible financial performance are better able to implement CSR as a strategic investment, which in turn increases firm value and strengthens market confidence. In the long term, market assesment efficiency and better capital allocation can support sustainable economic growth by channeling investment to companies that have strong financial performance and are socially responsible.